When do cosmic peaks, filaments, or walls merge? A theory of critical events in a multiscale landscape. Issue 4 (26th June 2020) - Cadiou, C; Pichon, C; Codis, S; Musso, M; Pogosyan, D; Dubois, Y; Cardoso, J-F; Prunet, S
ABSTRACT: The merging rate of cosmic structures is computed, relying on the ansatz that they can be predicted in the initial linear density field from the coalescence of critical points with increasing smoothing scale, used here as a proxy for cosmic time. Beyond the mergers of peaks with saddle points (a proxy for halo mergers), we consider the coalescence and nucleation of all sets of critical points, including wall-saddle to filament-saddle and wall-saddle to minima (a proxy for filament and void mergers, respectively), as they impact the geometry of galactic infall, and in particular filament disconnection. Analytical predictions of the one-point statistics are validated against multiscale measurements in 2D and 3D realizations of Gaussian random fields (the corresponding code being available upon request) and compared qualitatively to cosmological N -body simulations at early times ( z ≥ 10) and large scales ( 5 Mpc h^-1 ). The rate of filament coalescence is compared to the merger rate of haloes and the two-point clustering of these events is computed, along with their cross-correlations with critical points. These correlations are qualitatively consistent with the preservation of the connectivity of dark matter haloes, and the impact of the large-scale structures on assembly bias. The destruction rate of haloes and voids as a function of mass and redshift is quantified down to z = 0 for a Lambda cold dark matter cosmology. The one-point statistics in higher dimensions are also presented, together with consistency relations between critical point and critical event counts.